Time to cracking in concrete cover length due to reinforcement corrosion via a simplified fracture mechanics approach. (20th October 2020) - Jamshidi, F.; Dehestani, M.
Highlights: Fracture mechanics concept in the creation and propagation of corrosion-induced crack. The time needed to form corrosion products required to crack the concrete is obtained. Length of first crack created in the cover is predictable. Variation of CMOD during corrosion of rebar and cracking of cover are considered. Time and formation of cracking can be determined at any arbitrary length of the cover. Abstract: Determination of the concrete cover cracking time is one of the main parameters in estimating service life of concrete structures exposed to chloride-laden and other aggressive environmental conditions. The corrosion of reinforcing steel embedded in concrete occurs as a result of chloride attack or carbonation, and thus the increase in the volume of corroded reinforcing steel cracks the cover. In this paper, a theoretical model is proposed to calculate the cracking initiation and propagation time within the concrete cover. Increase in the volume of corroded reinforcing bar induces an internal pressure on the concrete around the bar, which brings on the cracking initiation and propagation through the cover. The internal pressure caused by corrosion is expressed in terms of steel mass loss, and then Faraday's law is implemented to account for the time in relationships. The time corresponding to creation of the first crack is obtained based on crack opening definition, and the crack propagation is approximated on the basis of fracture mechanics relationships. The merit of using fracture mechanics is that the crack propagation time can be calculated thru any desired length of the cover. In this model, the time required for corrosion products to fill the porous zone between concrete and steel bar, as well as the time needed to fill the void within the crack are also accounted for. Validity of the proposed model is investigated via comparing the results achieved in this model with those of experiments published in the literature.